The effects of whole-body vibration therapy on immune and brain functioning: current insights in the underlying cellular and molecular mechanisms - Ahuja, Gargi; Arauz, Y. Laurisa Arenales; van Heuvelen, Marieke J. G.; Kortholt, Arjan; Oroszi, Tamás; van der Zee, Eddy A. (Frontiers in Neurology, 2024)
Whole-body vibration (WBV) therapy is a way of passive exercise in which subjects are exposed to mild and well-controlled mechanical vibrations through a vibrating platform. For a long time, studies have focused on the effects and applications of WBV to enhance musculoskeletal performance in athletes and patients suffering from musculoskeletal disorders. Recent evidence points towards the positive effect of WBV on the brain and its therapeutic potential in brain disorders. Research being done in the field gradually reveals cellular and molecular mechanisms underlying WBV affecting the body and brain. Particularly, the influence of WBV on immune and brain function is a growing field that warrants an up-to-date and integrated review. Immune function is closely intertwined with brain functioning and plays a significant role in various brain disorders. Dysregulation of the immune response is linked to conditions such as neuroinflammation, neurodegenerative diseases, and mood disorders, highlighting the crucial connection between the immune system and the brain. This review aims to explore the impact of WBV on the cellular and molecular pathways involved in immune and brain functions. Understanding the effects of WBV at a cellular and molecular level will aid in optimizing WBV protocols to improve its therapeutic potential for brain disorders.